The Effect of Economic Determinants on Capital Structure with Market Conditions as a Control Variable (Case Study of IDX-Listed LQ 45 Manufacturing Company in 2015-2019) - Theresalin Theresalin; I Gusti Ketut Agung Ulupui; Harya Kuncara (Syntax Corporation Indonesia, 2022)
This study aims to examine the effect of economic determinants on Capital Structure as measured by Profitability, Company Size, Company Growth, Asset Structure, Liquidity, Effective Tax Rate, Business Risk in LQ 45 Manufacturing Companies Listed on the IDX in the 2015 – 2019 Period. The information used in this study came from the company's annual report, which was made available to the public via the Indonesia Stock Exchange or the company's website. Purposive sampling was employed, with a total sample size of 135 samples. Multiple linear regression analysis was utilized to analyze the data in this study. Classic assumption testing, such as descriptive analysis, chow test, Hausman test, LM test, data normality, heteroscedasticity, multicollinearity, and autocorrelation, had previously been performed on the data. The research data were found to be regularly distributed during the observation period. No variables diverged from the traditional assumptions based on the normality, multicollinearity, heteroscedasticity, and autocorrelation tests. This demonstrates that employing several linear regression equation models, the given data met the requirements. The variables of company size, company growth, effective tax rate, and business risk do not have a substantial effect on capital structure, according to this study. Capital structure is influenced by profitability, asset structure, and liquidity.